The Foreclosure Crisis and Neighborhood Sentiments: Learning from Las Vegas - Batson, Christie D. (Social justice, 2013)
The article discusses research findings on home foreclosures in Las Vegas, Nevada, and their effect on community attachment and cohesion as experienced by those in foreclosure and those living in foreclosure-plagued neighborhoods. Topics include survey results on indicators measuring neighborhood contentment in relation to foreclosure rates and similar nationwide patterns for demographics and foreclosures.